PEMANFAATAN E-MODUL DENGAN FLIP PDF PROFESSIONAL BERBASIS GAMIFIKASI DALAM MENINGKATKAN PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Ariswan; Firman; Desyandri (STKIP Subang, 2024)
In today's digital era, digital learning resources have become an important tool in education, especially in mathematics learning in elementary schools. With the use of technology, students can access a variety of interactive and engaging materials, which can increase their motivation to learn (Melati et al., 2023). To help focus more, you can use a gamification-based E-module that contains material until evaluation that is adjusted to the curriculum using gamification stages used by researchers using animated images that have never been researched before. The research method used in this study uses a descriptive-qualitative research method with an approach, namely literature study. Data is obtained through the analysis of various sources, such as journals and books related to the research objectives. E-modules can accompany the learning process because of the quality of use. The purpose of this study is to determine the development and effectiveness of learning to E-modules with Flip PDF Professional-based gamification.